Online Trading Phenomenon In Indonesia - Jatnika, Sandy Nata; Hendrian , Hendrian; Asnawi, Said Kelana (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
The study aims to identify and analyze the mechanisms of online trading conducted by Indonesian Air Force (TNI AU) personnel and to investigate their motivations for engaging in online trading. This research is a qualitative study conducted within the TNI AU environment. It adopts the perspective of the Reasoned Action Theory (TRA) in analyzing online trading. TRA is driven by several factors, such as attitude toward behavior, subjective norms, and actual behavior. Methodology/approach – A survey that included information about online trading was used to collect data. The study was conducted through in-depth interviews with three individuals involved in online trading. Findings – The results show that the impact of online trading within the TNI AU environment is predominantly negative. This is attributed to the inability to process information effectively, as well as the lack of financial and informational literacy, which leads to errors in decision-making and the selection of online trading platforms. Novelty/value – As soldiers' inability to resist lifestyle demands and their temptation by social media advertisements and influencers who create content showcasing easy profits through online trading.